Topography of Lectin Binding Sites in Celiac Sprue - Hugh J Freeman (Canadian Journal of Gastroenterology, 1992)
Lectins are ubiquitious, naturally occurring proteins largely derived from planes that are present in the human diet. They are released from food during mastication and digestion to remain biologically intact during passage through the small intestine. In this study, the topographic distribution of binding sites in the small intestine for six different lectins (derived from wheat germ, castor bean, gorse, horsegram, jackbean and peanut) were explored in 16 patients with celiac sprue a long with controls. For each lectin, the pattern of binding in the small intestinal biopsy specimens was distinct and specifically inhibited by a different carbohydrate residue. Lectin labelling patterns were different for both controls and celiac patients. in addition, the epithelial cell membrane surface and goblet cells exhibited a gradient of fluorescence intensity along the crypt-villus column. This gradient appeared to parallel the degree of enterocytic differentiation consistent with the concept that sequential addition of sugar residues to form completed oligosaccharide side chains occurs with enterocytic differentiation and maturation. These results also suggest that the process of epithelial cellular differentiation, although present in celiac enterocytes, is altered substantially.